Functional outcome of steroid injection in trigger finger between professional and service workers - Ahmad Ismani, Muhamad Syafiz; Ismail, Raffael; Khalid, Kamarul Ariffin; Mor Japar Khan, Ed Simor Khan (2018)
INTRODUCTION Trigger finger (TF) is one of the commonest causes of disabling hand pain in orthopedics and affects individuals regardless of their daily activities. It is characterized by inflammatory changes in the retinacular sheath and peritendinous tissue at the fibro-osseous tunnel which result of pain and triggering of the finger due to the discrepancy between the diameter of the flexor tendon and its sheath at the A1 pulley. This study aims to evaluate the degrees of responses of TF upon steroid injection among professionals and service workers. METHODS An observational cohort study, evaluating the functional outcome of steroid injection among professionals and service workers in TF grade I, II and III using the Michigan Hand Outcomes Questionnaire (MHQ) in three separate visit; pre injection, post injection 6 and 12 weeks. The classification of professional and service group is according to the Malaysia Standard Classification of Occupation 2013 (MASCO). Both groups will undergo physiotherapy post steroid injection for optimum results. RESULTS 44 fingers in each group, with various stages of TF underwent steroid injection. Overall MHQ score in both groups show a good functional outcome between pre injection and post injection at 12 weeks, with P values <0.001. Comparing the grades of TF, the data analysis shows good functional outcome between pre injection and post injection at 12 weeks, with P values <0.01 in both groups. There was only 1 (2.2%) patient in service group who undergo open release after the second visit following the steroid injection treatment. DISCUSSION Steroid injection delivers a good functional outcome and pain relief in TF even up to stage III with between professionals and services workers up to 12-weeks duration. Steroid injection is 1 of the preferred treatment methods as it is less invasive compared to open release and subcutaneous inoculation technique is adequate to yield excellent results. CONCLUSION Steroid injection is an excellent option of treatment TF for professional and service workers allowing early return to work with no differences in outcome regardless of the stage. The treatment is shown to have a good functional outcome in both groups.